Роль циркулярної економіки в досягненні цілей сталого розвитку - Болтянська, Лариса Олексіївна; Сиротюк, Ганна Володимирівна; Boltianska, Larysa; Syrotiuk, Hanna (Запоріжжя : Видавничий дім «Гельветика», 2024)
UA: У статті аналізується циркулярна економіка як альтернативна лінійна модель, що базується на раціональному використанні ресурсів, переробці та мінімізації витрат. Підкреслено актуальність її впровадження в Україні для стабілізації економіки, створення робочих місць та підвищення ресурсоефективності. Окреслено виклики й можливості, а також визначена роль циркулярної економіки в досягненні Цілей сталого розвитку ООН. /// EN: The article examines the concept of a circular economy as an effective alternative to the traditional linear economic model. The circular economy is based on the principles of rational use of resources, reuse, recycling and waste minimization. It is aimed at creating closed cycles of production and consumption, which allows to significantly reduce the negative impact on the environment, increase resource efficiency and promote sustainable development. The article pays special attention to the relevance of implementing a circular economy in Ukraine. Against the background of global challenges, such as depletion of natural resources, increasing waste, and climate change, the transition to a circular economy model is an integral part of modern environmental policy. In the conditions of martial law and post-war recovery, the circular economy can become a powerful tool for stabilizing the economy of Ukraine, stimulating innovation, creating jobs and integrating into the European economic space. The article analyzes the main challenges and opportunities for implementing the principles of a circular economy in Ukraine. The authors emphasize that the development of processing enterprises, the reuse of resources and the introduction of innovative technologies can contribute to reducing the costs of enterprises, reducing dependence on imported raw materials and increasing export potential. In addition, the emphasis is placed on the role of the circular economy in achieving the UN Sustainable Development Goals. It is indicated that the implementation of circular practices helps to implement tasks related to combating climate change, increasing water efficiency, developing renewable energy, and reducing food waste.
The role of the circular economy in achieving the sustainable development goals
Keywords: циркулярна економіка; сталий розвиток; модель «виробництво-використання-утилізація»; цілі сталого розвитку; ресурсозбереження; circular economy; sustainable development; "production-use-recycling" model; Sustainable Development Goals; resource conservation